Use of TNF Inhibitors in Rheumatoid Arthritis and Implications for the Periodontal Status: For the Benefit of Both? - Zamri, Fatima; de Vries, Teun J. (Frontiers in Immunology, 2020)
The inflammatory disease rheumatoid arthritis (RA) and periodontitis show similarities in misbalances of cytokine levels, such as tumor necrosis factor-α (TNF-α). RA has been treated for two decades with TNF-α inhibitors which are effective by blocking TNF-α’s destructive action. Since RA and periodontitis show similarities in high levels of TNF-α, the periodontal status of RA patients may improve with the use of anti-TNF-α therapy. To assess this, a systematic review with special emphasis on duration of therapy was performed to evaluate the effect of anti-TNF-α treatment on the periodontal status of RA patients. Overall, studies showed an improvement in periodontal health with anti-TNF-α therapy. When analyzed over time (6 weeks to 9 months), it became apparent that initial improvements concerned bleeding on probing (BOP) and gingival index (GI) after therapy duration of 6 weeks. Periodontitis parameters that improved after prolonged treatment were: probing pocket depth (PPD) after 3 months and clinical attachment level (CAL) after 6 months. In conclusion, this systematic review reveals that anti-TNF-α TNF treatment is therefore not only beneficial for rheumatic joints but also for the gums of rheumatoid arthritis patients. We propose that the sequential tissue recovery due to anti-TNF-α TNF therapy progresses as follows: (1) block of diapedesis by lowering vessel permeability, (2) fewer leukocytes in the inflamed tissue, (3) reduced proteolytic activity and subsequent repair of collagen fiber functionality and normalization of osteoclast activity. Clinically, this could lead to a decrease in bleeding on probing and ultimately in an improved clinical attachment level.